Quality management : a project management perspective - Ingason, Helgi Thor (New York : Routledge, 2020)
'The implementation of quality management is a project and evolves as a result of how projects are planned, executed and closed. This book explores quality management from a project management perspective, based on the authors long experience of teaching and practicing, including the implementation and operation of quality management systems within various types of organisations. The author explores the origins of quality management as a discipline, it's appearance in the present form and how quality management can be implemented and applied in all kinds of organisations to achieve stability and better results. The basic principles of quality management and the ISO9001 quality management standard are discussed and explained from a broad perspective, with illustrative examples from different types of organisations. Quality Management offers a global, accessible guide for undergraduate and postgraduate university students. Written clearly and with illustrative examples, it will also appeal to all those interested in project management and wishing to expand their knowledge base'--
Includes bibliographical references and index.
Buku bacaan asas Fakulti Ekonomi dan Pengurusan.
Keywords: Total quality management; Quality control; Project management